Financial Development and Sectoral Productivity : New Insights from Selected G20 Economies - Garg, Niti Khandelwal (Indian Journal of Finance, 2025)
Purpose : The study empirically investigated the linkages between financial development and sectoral labor productivity of a group of seven major advanced economies (G7) and the major emerging economies, viz., India, South Africa, Indonesia, Brazil, Mexico, South Korea, China, and Australia, over the period from 1980–2017 in a multivariate model. Design/Methodology/Approach : The econometric techniques of cross-sectional dependence test, second-generation panel unit root tests, panel cointegration, and augmented mean group estimator were used. Findings : The study found that while the development of financial markets is conducive to productivity growth of both manufacturing and market services of emerging economies, they have a larger impact on market services than the manufacturing sector. Another key finding of the study was that while financial development influences the productivity of emerging economies positively and significantly, the impact is either negative or insignificant for the G7 economies. Thus, the study found that development in financial markets may not affect the productivity of various sectors uniformly. Moreover, the continuous expansion of the financial system may not be beneficial for an economy but may become detrimental after a point. Practical/Policy Implications : The differential effect of finance on labor productivity across sectors entails the policies specific to sectors in emerging economies. Moreover, the negative impact of financial development on productivity in developed countries emphasizes the need for improvement in the quality of finance rather than the mere size of finance. Originality/Value : The study used advanced non-stationary panel data techniques that incorporate heterogeneity and cross-sectional dependence to examine the influence of financial development on labor productivity at the sectoral level in the recent period for both emerging and advanced economies of the world.